Diálogos matemáticos no ensino remoto: entre dificuldades e possibilidades - Marques, Luciana Maria Estevam (2022)
The main objective of this dissertation is to understand how mathematical dialogues take place remotely in a school that transforms itself daily into a Learning Community. To do so, we invited members from the school community to participate in mathematical tertulias with the work "The Man who counted" by Malba Tahan (2020 edition). The development of this theme enabled reflections about social mathematics, so that the dialogical remote spaces provided the opportunity for this investigation. The contributions of Dialogical Learning (Aubert and collaborators, 2020), were essential for beginning the dialogues, while considering the heterogeneity of the group participating in the research that enabled transformations during the investigative process. The research that we presented has a qualitative character, and for that we used the Critical Communicative Methodology (Goméz and collaborators, 2006), which defends the importance of knowing the social reality in order to transform it. Based on methods, it is possible to identify the needs analyzed in intersubjectivity. Thus, we conducted our research in a municipal public school that has become a Learning Community since 2017, when the municipality of Mogi Guaçu - SP, in partnership with the Núcleo de Investigação e Ação Social Educativa (NIASE) of São Carlos, offered network training for principals and pedagogical coordinators and since then, successful educational actions have taken place at school with the intensive participation of families and the local community. The participants of the research were students, school collaborators, managers, mothers of students, and teachers who work in the early and final years of elementary school. The analyses were articulated with our theoretical references that briefly discussed mathematics, considering authors such as Skovsmose, Palomar, D’Ambrósio, Paulo Freire, among others who discussed mathematics from a critical and social perspective. At the end of our analyses, we revisited our research problem, which sought to answer about the difficulties and potentialities of a remote dialogical environment focused on Mathematics, and we register that some obstacles made the meetings more complicated, for example, the access to online platforms, the absence of a body reading during the experiences in mathematical tertulias, and the appearance of sudden commitments that made some collective meetings difficult. About the aspects that facilitated the dialogues, we can mention the permanence of the message group, being open all the time for contributions, and also the facility of access for those who could connect. However, it is worth remembering that this also becomes an excluding factor, if we consider that not everyone has access to technology.